Predicting Perceived Stress and Resilience: The Role of Differentiation of Self - Süloğlu, Dilay; Güler, Çiğdem Yavuz (Ter Media, 2021)
Differentiation of self is a process that describes an individual’s ability to act by separating emotions and thoughts at the internal level as well as the ability to be activated by maintaining the self in intense relationships through the establishment of a balance between autonomy and closeness at the level of interpersonal relations. The aim of this study was to determine the role of the differentiation of self – which is one of the basic concepts of the Bowen family systems theory – in predicting perceived stress and resilience.
Keywords: Bowen Family Systems Theory; Differentiation of Self; Perceived Stress; Resilience